Influence of Thermal Stress and Seasonal Variations on Basal and Post-Service Progesterone Profile in Postpartum Dairy Cows under the Humid Tropical Climate - Cholakkal, Ibraheem Kutty (The Indian Journal of Animal Reproduction, 2024)
The present study of progesterone (P4) levels and its seasonal variations intended to assess the influence of thermal stress (TS) on the postpartum PP fertility of cows. Seasonal variations of basal and post-service (PS) P4 levels were compared with climatic variables and stress indicators in serum. Basal and three PS interval P4 levels did not vary significantly between seasons, whereas the mean P4 level of PS intervals varied significantly between seasons with the lowest during summer. Also, P4 levels showed significant seasonal variation in conceived animals with the highest value before summer. While basal P4 levels showed a significant negative correlation with ambient temperature, PS P4 levels did not show a significant correlation with climatic, physical, and biological parameters studied. It is concluded that even though ovaries are functional throughout the early PP period, seasons of TS appear to suppress progesterone secretion and fertility performance of cross-bred dairy cows under the humid tropical climate.
Keywords: Crossbred Cow; Fertility; Progesterone; Season; Thermal stress